(untitled) (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2017)
Snow should be accounted in electromagnetic fields' risk assessment, especially in Nordic countries where in winter months snow precipitation and coverage may significantly affect the propagation of microwaves. The risk assessment should be always carried out under worst case scenario conditions, including the reflective properties of the surfaces surrounding the antenna. In this study fresh snow microwave reflectance properties were investigated at the mobile communication bands from 1700 to 2700 MHz.The investigation revealed that reflection loss from snow is more dependent from the frequency than from the thickness of snow coverage. Amongst mobile communication bands, the strongest microwave reflection (reflection loss only 3.2dB) was registered at WiFi2G band. Averaging all the snow thicknesses, the highest reflection loss occurs at GSM1800UL (1710-1785 MHz) and UMTS2100DL (2110-2170 MHz) bands. The least attenuation of reflection occurs in adjacent DECT band.